Is There a "European Family Law"? - Scherpe, Jens M (Victoria University of Wellington Law Review, 2023)
Europe consists of many very different jurisdictions and there is no institution that actually has the legislative power to create family laws for member states of the European Union, let alone Europe as a whole. Therefore, one could assume that no common "European Family Law" exists. However, this article argues that while there of course cannot be a full "European Family Code", some core elements of European Family Law have grown organically through similar social and legal developments, while other core elements have been established by institutional actions as well as court decisions. Together, these core elements represent fragments of a growing body of European Family Law.